100% information literacy success - Taylor, Terry (Thomson Delmar Learning, 2007)
This textbook, the fourth entry in the "100% Success" series, introduces students to the foundational concepts of information literacy as described by the American Library Association, empowers students to become information-literate, and prepares them for information-seeking in the workplace. The six chapters offer a step-by-step guide to defining an information need; finding, accessing, and evaluating information; and navigating through the legal, ethical, and communication dynamics of information-seeking. To facilitate the learning process, each chapter features learning objectives, a practical scenario, reflection questions, critical thinking questions, individual and group activities, self-assessment, and references. The periodic "hints" and "questions to ask" boxes encourage critical thinking. Many of the scenarios, questions, and activities involve workplace situations germane to the student's field of study, emphasizing the importance of information literacy for lifelong learning. The online companion features quizzes and web resources to complement each chapter. Well organized, easy to read, and comprehensive, this practical guide is highly recommended for those teaching college-level information literacy